THE INFLUENCE OF THE MANAGEMENT REGULATION OF PNBP AND OPERATIONAL BUDGET REQUIREMENTS OF TNI AL Hospital ON HEALTH SERVICES - Kusuma, Ilham Ganda; Sarililah, Linaningsih; Subhan, Hadi; Ruspiana, Evi; Lukman, Muhammad (Journal of Industrial Engineering & Management Research, 2020)
Health is a basic need of every human being and is the capital of every citizen and every nation in achieving its goals and achieving prosperity. A person cannot fulfill all the necessities of life if he is in an unhealthy condition. So that health is the capital of each individual to continue his life properly. The government has the responsibility to ensure every citizen gets quality health services according to their needs. The type of research used in this research is quantitative research methods. Quantitative research is a type of research that basically uses a deductive-inductive approach. This approach departs from a theoretical framework, the ideas of experts, as well as the understanding of researchers based on their experience, then it is developed into problems and solutions that are proposed to obtain justification (verification) or assessment in the form of support for empirical data in the field. has a partial determination coefficient (R Square) of 0.847, this means that the PNBP management regulation variable contributes 84.7% in explaining the PNBP management regulation variable. Meanwhile, the correlation coefficient value is R = 0.921, which means it is greater than 0 (Î²1 > 0). Meanwhile, the significance level is 0.00 which means it is smaller than 0.05. It can be concluded that the PNBP Management Regulation has a partially positive effect on Health Services, while the results of the F-Test at the level of significant (a) = 0.05 can be seen that the F count = 230,792 (greater than F table = 3.15) with probability = 0.000 < a = 0.05, then Ho is rejected, Ha is accepted, which means that the variable PNBP management regulation, the operational budget needs of the Indonesian Navy together have a positive effect on health services.